Pengaruh Media Kartu Kata Bergambar Terhadap Kemampuan Membaca Permulaan Siswa Kelas I SD Negeri 42 Pekanbaru - Dwi Intan Beliana; Siti Quratul Ain (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
A learning process that relies only on the lecture method makes learning less engaging for students, which contributes to students' low beginning reading ability. This research aimed to determine the effect of using picture word card media on the beginning reading ability of first-grade students at SD Negeri 42 Pekanbaru. This research is quantitative research with a pre-experimental type, using a one group pretest-posttest design. The research sample consisted of 29 students of class I.D, selected through a saturated sampling technique. The data collection techniques used were tests, observation, and documentation. The instrument was tested for content validity, item validity, and reliability before use. The data analysis technique used descriptive analysis and hypothesis testing using the Paired Sample t-Test, which had previously been tested for normality using the Shapiro-Wilk formula. The results of the research show that there is an effect of using picture word card media on the beginning reading ability of class I students at SD Negeri 42 Pekanbaru. The average score increased from 47.686 in the pretest to 83.252 in the posttest. The results of the Paired Sample t-Test show that the value tcount = 26.978 > ttable = 2.048 with a significance of 0.000, which is smaller than the 5% significance level (0.000 < 0.05). This proves that there is a significant effect of using picture word card media on the beginning reading ability of class I students at SD Negeri 42 Pekanbaru.